ANALISIS TERHADAP TINGKAT REVENUE PERUSAHAAN PRODUSEN TANAMAN HIAS TERHADAP PENGELUARAN BIAYA PROMOSI SEBAGAI BAGIAN DARI SISTEM PENJUALAN PRODUKNYA - Rustam Hakim Manan (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2016)
Enterprises producers of ornamental plants mostly in the form of UKM that has not been touched by the thought of utilizing advertising as a means of promotion merchandise. A phenomenon that perceives that the cost of advertising spending for the promotion, will bring revenue burden for entrepreneurs producers of ornamental plants. Therefore, the author tries to see how the level of income of a company producer of the promotional expenses. Data obtained books adapted by Carter Hill, William Griffiths, George Judge, in the book Undergraduate Econometrics, John Willey & Sons Inc., New York, 1988. The data are taken as many as 15 pieces with variable between the levels of income/revenue expenditure promotional costs. That is the level of income is influenced by promotional expenses. Thus the dependent variable (Y) is the income and promotion expenses (X). This paper will attempt to provide an analysis of the level of revenue company producers of ornamental plants against promotion expenses as part of the system sales of its products. The assumption is estimated that revenue will increase when enlarged promotional expenses. The purpose of the description in this paper is to discuss the hypothesis of economic phenomena, especially on the behavior and function of the company's revenue with the cost of sale (in this case the cost of advertising). The methodology used is through the approach of econometrics at the company's plant landscaping and regression analysis (linear) with SPSS method. From the discussion, we concluded among other things, income / revenue are highly dependent on spending promotional / advertising. Therefore if the company will still generate the maximum benefit it is necessary expenses advertising costs.